2022
DOI: 10.3390/agronomy12020517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Tillage Managements on CH4 and N2O Emissions from a Double-Cropping Rice Field in Southern of China

Abstract: Soil carbon (C) content plays an important role in maintaining or increasing soil quality and soil fertility. However, the impacts of different tillage and crop residue incorporation managements on greenhouse gas (GHG) emissions from paddy fields under the double-cropping rice (Oryza sativa L.) system in southern China still need further study. Therefore, a field experiment was conducted to determine the impacts of different short-term (5-years) tillage and crop residue incorporation managements on soil organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, NT can improve soil carbon stocks, nutrient content, and structural stability (Hungria et al 2009;Pu et al 2019), thereby promoting greater soil microbial activity than that observed in CT (Souza et al 2015). However, the impact of NT on GHGs is complex, potentially reducing CH 4 emissions and overall GWP, yet in some instances, increasing N 2 O emissions (Tang et al 2022). A previous comparison between NT and CT showed a complex pattern: NT led to higher CH 4 emissions in winter and lower N 2 O and CO 2 emissions in summer (Vilakazi et al 2021), with potential reductions in GHG intensity (Zhang et al 2014) and enhanced soil organic carbon (SOC) content (Palm et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NT can improve soil carbon stocks, nutrient content, and structural stability (Hungria et al 2009;Pu et al 2019), thereby promoting greater soil microbial activity than that observed in CT (Souza et al 2015). However, the impact of NT on GHGs is complex, potentially reducing CH 4 emissions and overall GWP, yet in some instances, increasing N 2 O emissions (Tang et al 2022). A previous comparison between NT and CT showed a complex pattern: NT led to higher CH 4 emissions in winter and lower N 2 O and CO 2 emissions in summer (Vilakazi et al 2021), with potential reductions in GHG intensity (Zhang et al 2014) and enhanced soil organic carbon (SOC) content (Palm et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when analysing the impact of greenhouse gases from the transport sector, the total emissions are expressed in equivalent CO 2 e, taking into account the greenhouse potential values of the constituent gases. The CO 2 e emission value was calculated from Formula (3): Global warming potential (GWP) is generally considered a vital indicator for the effects of GHG emissions, with the GWP of CO 2 defined as 1 [23][24][25]. The GWP values chosen for CH 4 and N 2 O are values over a 100-year time horizon relative to CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our findings revealed that average annual soil carbon sequestration increased in the three tillage treatments, which suggests that soil carbon sequestration reduces the CF of rice fields. This positive effect mainly stems from the return of straw to the experimental plots in recent decades and cannot be explained alone by the short period over which our experiments were conducted (2 years; Huang et al, 2013;Tang et al, 2022). Some studies have also suggested that soil carbon sequestration reduces the CF in winter wheat-summer maize rotation and double-cropping rice systems (Shang et al, 2021;Sun et al, 2022).…”
Section: Carbon Footprintmentioning
confidence: 91%